Altered Pattern of Naïve and Memory B cells and B1 Cells in Patients with Chronic Granulomatous Disease - Monireh Mohsenzadegan (Iranian Journal of Allergy, Asthma and Immunology, 2014)
Chronic  granulomatous  disease (CGD)  is a rare primary immunodeficiency disorder characterized by a greatly increased susceptibility to severe fungal and bacterial infections caused  by  defects  in  NADPH   oxidase  of  phagocytic  cells. We  aimed  to  investigate immunophenotype alterations of naïve and memory B cells and B1a cells in peripheral whole blood from Iranian patients with CGD. Flow cytometric analysis was performed  on  peripheral blood  samples from  31 CGD patients and 23 healthy controls (HC) to study naïve (IgD+/CD27-), memory (CD27+) B and B1a (CD5+) cells. Soluble CD27 (sCD27) and immunoglobulins were also measured by ELISA and the nephelometric method, respectively. We found significantly higher levels of naïve B cells and B1a cells but lower levels of memory B cells in CGD patients compared to HC. There was no significant difference in soluble CD27 (sCD27) alteration between CGD patients and HC. Our findings suggested a role for NADPH oxidase in process of B cell differentiation and impairing conversion of naïve B cells to  memory B cells and altered B1a cells in CGD patients.  Increased   susceptibility  of   CGD   patients   to   opportunistic   infections   and autoimmune disorders could be partly explained by the altered phenotype of B lymphocytes in these patients.